2013
DOI: 10.1002/adsc.201300587
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Desulfitative Direct CH Arylation of Electron‐Deficient Polyfluoroarenes with Sodium Arenesulfinates

Abstract: The palladium-catalyzed direct arylation of electron-deficient polyfluorobenzenes was developed in the presence of silver carbonate and trisodium phosphate. This protocol allowed use of both electron-deficient and electron-rich aromatic sulfinic acid sodium salts as arylating reagents for the direct arylation of a variety of polyfluoroarenes to produce fluorobiaryls in good to excellent yields, providing a complement to the existing methods for the direct arylation of polyfluoroarenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 52 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…Indeed, they can be prepared by addition of organometallic reagents to sulfur dioxide or DABSO (1,4‐diazabicyclo[2.2.2]octane bis(sulfur dioxide) . For instance, sodium sulfinates were used advantageously in coupling reactions as “arene donors” and for sulfonamide synthesis by copper‐catalysed oxidative coupling with amines . Recently, Yang et al described another non‐catalysed approach to preparing sulfonamides using sodium sulfinate and an amine in the presence of iodine as oxidant in ethanol , …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they can be prepared by addition of organometallic reagents to sulfur dioxide or DABSO (1,4‐diazabicyclo[2.2.2]octane bis(sulfur dioxide) . For instance, sodium sulfinates were used advantageously in coupling reactions as “arene donors” and for sulfonamide synthesis by copper‐catalysed oxidative coupling with amines . Recently, Yang et al described another non‐catalysed approach to preparing sulfonamides using sodium sulfinate and an amine in the presence of iodine as oxidant in ethanol , …”
Section: Introductionmentioning
confidence: 99%
“…[4] Since these earliest examples, al arge number of contributions have for the direct arylation of electron-deficient arenes. [5] Mosto ft he efforts focused on the findingo fa lternative coupling partners to aryl halides such as tosylates, [6] diaryliodonium salts, [7] boronic acids, [8] ArSO 2 Na, [9] carboxylic acid, [10] or simple arenes under oxidative conditions. [11] Other transition metals have also been successfully used for theseC ÀCbond formations.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Other transition metals have also been successfully used for theseC ÀCbond formations. [12] These procedures mainly employed pentafluorobenzene, [3,6,7,[9][10][11][12][13] tetrafluorobenzene, [6a,b, 14] trifluorobenzene, [15] or even difluorobenzene [16] as starting materials,a st he use of monofluorobenzeneg enerally displayed al ow reactivity.F or example, Fagnou reported that the arylation of fluorobenzene in the presence of 1-bromo-4-methylbenzenep roceeded in only 8% yield ( Figure 1A). [3a] In the recent literature, only af ew examples overcome this low reactivity of fluorobenzenes and allowed the formation of monofluorobiphenyls in high yields (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, sulfinates have received increased attention after early reports on their coupling reactions by Garves,26 and Selke and Thiele27 that used stoichiometric amounts of palladium were largely overlooked. The use of sulfinates in Heck‐like transformations,28–32 addition reactions to (hetero)double bonds and triple bonds,3339 direct arylations4042 and related reactions,43 have in common the replacement of the electrophilic cross‐coupling partner with an aryl sulfinate. The ability to replace the nucleophilic coupling partner with sulfinates is an emerging field of research only preceded by a patent from the 1990s;44–49 many of these contributions were reported by the group of Deng.…”
Section: Introductionmentioning
confidence: 99%